Dark Academia: Despair in the Neoliberal Business School - Fleming, Peter (Journal of Management Studies, 2020)
Although it was supposed to be a faculty 'Away Day', we were crammed into a room only a few hundred metres from the business school.Budgets were tight and departmental austerity was in full bloom.The Dean took centre stage and gave a talk largely consisting of corporate buzzword phrases: "significant stretch targets"; "get our friends in the tent"; "the aha effect"; "global mindset"; "clean up the box we live in"; "big buckets you then sharpen".A bewildered colleague beside me leant in and whispered, "these Away Days are so bloody depressing".I nodded in agreement, mirroring the forlorn faces around me.But worse was to come.Next on the agenda was a team building exercise involving African drumming.As we banged away on our cheap djembes in embarrassment, the Dean was nowhere to be seen.Exhausted, tyrannised by office email and under pressure to meet performance targets, the Away Day felt like some kind of cruel joke.